Programs trades and trade regulation: An evidence of the Korean securities market. Issue 1 (10th September 2019) - Eom, Cheoljun; Jordan, Steven J.; Lee, Woo‐Baik; Park, Jong Won
Abstract: This study addresses the effects of program trade regulation during large market moves. To address this issue, we analyze the effect of sidecars (halts that only affect program trades) on trade imbalance using Korean intraday data. We find that sidecars, as currently designed to halt all program trades, are not effective at controlling trade imbalance around volatile markets. Resolution of trade imbalance is more effective when program trade is unrestricted. Program trade, at least a subset, provides liquidity when it is at a premium. We conclude that current sidecars should be more carefully crafted as some program trades are market stabilizing.